SYSTEM OF PUBLIC PROCUREMENT OF GOODS, WORKS AND SERVICES IN UKRAINE - NAHAICHUK, Viktoriia; MAZUR, Vitalii; HAVRYSH, Natalya (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the theoretical foundations of public procurement, defines the main concepts used in their implementation, and the role of procurement in the economy, and provides their classification. Since the public procurement system has a significant impact on the national economy, the strategic, innovative, administrative, social, regulatory and incentive functions of the customer country are taken into account. In order to systematize information about the current public procurement system in Ukraine and conduct further analysis, its organizational model was considered. One of the main elements of the public procurement system, the proper creation of which depends on the targeted and effective use of national financial resources, is the needs of the state (local self-government bodies), in connection with which it is necessary at the legislative level in Art. 1 of the Law "On Public Procurement" to establish the concept of  "state (municipal) needs"; it is necessary to make changes to the concept of "public procurement", because the existing concept does not fully reflect the content of the system and is very difficult to understand. In the process of theoretical research of the public procurement system, one should also take into account such important elements of this system as the financing of state (municipal) needs in accordance with the budget legislation of Ukraine.
Keywords: budget funds; state orders; procurement model; public procurement system; bidding